"You Were Strangers in the Land of Egypt" (Exod 22:20): Notes on the Attitude(s) towards Foreigners in Ancient Egypt - Taterka, Filip (The Biblical Annals, 2024)
The article discusses various attitudes towards foreigners that can be perceived in ancient Egyptian material. It is argued that there was no single and unchangeable attitude towards foreigners throughout ancient Egyptian history, but instead that Egyptian attitudes to foreigners changed over time due to various historical and social factors. It is also argued that these attitudes reflected a constant negotiation between the traditional and stereotypical perception of foreigners as enemies of the Egyptian state and more nuanced approaches in which foreigners could have a number of roles to play in Egyptian society, which often led to significant transformations of Egyptians’ self-identity. Therefore, the traditional image of ancient Egypt as a highly xenophobic culture is called into question.